Microwave Processing of Black Mass from Spent Lithium-ion Batteries - Hossain, Mozammel (My University, 2024)
In this Master’s thesis, the effect of microwave radiation on the black mass derived from spent lithium-ion batteries was analysed with an aim of discovering an energy-efficient, and cost-effective route for recycling lithium-ion battery, and recovering valuable metals. Microwave heating requires less amount of energy compared to conventional heating while producing larger impact on the cracking of cathodic structures. Due to the inside-out heating mechanism volumetric and selective heating is possible with microwave radiation which increases the formation of easily leachable elements from the mixture of anode and cathode. Theoretical section of this manuscript described the components of a battery. The chemical composition of the cathode and anode along with other parts such as electrolyte, current collector, and separator was being presented. Then the recent scenario of recycling and what are the industries that have already been taking the initiative was mentioned. After that, different methods of battery recycling were discussed. After taking their advantages and disadvantages into consideration, a combination of two processes were analysed. Finally, the theory behind microwave heating, their usage in different material processing sectors, and their application in battery recycling were discussed. The results aligned with our objective of the thesis. After thermal treatment of the pre-processed samples in a microwave, the characterization was done using XRD, and SEM-EDX. On the other hand, to understand the thermal behaviour of those samples, TGA-DSC-MS was done as well in two different atmospheres (air, and inert). Results showed that the burning of the raw samples was better within the air atmosphere, because of the availability of oxygen. However, in an inert atmosphere, more elements were found in metallic form rather than in their oxide forms. Meanwhile, microwave radiation can enhance the breakdown of the cathode’s structure. Therefore, the cathode materials were broken down into separate metals and metallic oxides just after processing at 400 ℃. The in-creasing temperature made the formation of metals within the sample easier and at the final stage of processing which was at 1200 ℃ metallic elements were dominant in the sample.
Keywords: microwave heating, recycling, battery, metal recovery, pyrometallurgy